2022
DOI: 10.1111/all.15579
|View full text |Cite
|
Sign up to set email alerts
|

Precision cut intestinal slices, a novel model of acute food allergic reactions

Abstract: Background Food allergy affects up to 10% of the pediatric population. Despite ongoing efforts, treatment options remain limited. Novel models of food allergy are needed to study response patterns downstream of IgE‐crosslinking and evaluate drugs modifying acute events. Here, we report a novel human ex vivo model that displays acute, allergen‐specific, IgE‐mediated smooth muscle contractions using precision cut intestinal slices (PCIS). Methods PCIS were generated using gut tissue samples from children who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Lake et al provided a normalized approach and compared nuclear and whole-cell expression data ( Lake et al, 2017 ; Lake et al, 2019 ). SnRNA-seq might be more widely applied in clinical practice because it is tolerant to sample sources, such as temporal neocortical tissues ( Busch et al, 2022 ), human hippocampus ( Su et al, 2022 ), gut tissue samples ( Hung et al, 2022 ), frozen or hard-to-dissociate tumors ( Slyper et al, 2020 ). One study showed that snRNA-seq performed better on inflammatory fibrotic tissues than scRNA-seq.…”
Section: Single-cell Sequencing Technologymentioning
confidence: 99%
“…Lake et al provided a normalized approach and compared nuclear and whole-cell expression data ( Lake et al, 2017 ; Lake et al, 2019 ). SnRNA-seq might be more widely applied in clinical practice because it is tolerant to sample sources, such as temporal neocortical tissues ( Busch et al, 2022 ), human hippocampus ( Su et al, 2022 ), gut tissue samples ( Hung et al, 2022 ), frozen or hard-to-dissociate tumors ( Slyper et al, 2020 ). One study showed that snRNA-seq performed better on inflammatory fibrotic tissues than scRNA-seq.…”
Section: Single-cell Sequencing Technologymentioning
confidence: 99%
“…This finding highlights the importance of early introduction in potentially halting or reversing the progression of the specific FA being treated, in addition to prevention. Tissue‐specific effects of OIT in humans are under‐researched and may play an important role 99,100 …”
Section: Mechanisms and Potential Biomarkers Of Food Allergy Immunoth...mentioning
confidence: 99%
“…Tissue-specific effects of OIT in humans are under-researched and may play an important role. 99,100 SLIT utilizes a 100-fold lower dose of allergen (maintenance dose as reported for inhalant allergen SLIT. 101,102 Such mechanisms include the uptake of allergens by oral antigen presenting cells (APCs) from the sublingual mucosa.…”
Section: Mechanis Ms and P Otential B Iomarker S Of Food Allergy Immu...mentioning
confidence: 99%
“…98 Tissue-specific effects of OIT in humans are under-researched and may play an important role. 99,100 SLIT utilizes a hundred-fold lower dose of allergen (maintenance dose 2-5mg/day). It takes advantage of local oral tolerance mechanisms as reported for inhalant allergen SLIT.…”
Section: Lessons From Rodent Data On Food Allergymentioning
confidence: 99%